2018
DOI: 10.1002/aelm.201700655
|View full text |Cite
|
Sign up to set email alerts
|

Seeded Space‐Limited Crystallization of CH3NH3PbI3 Single‐Crystal Plates for Perovskite Solar Cells

Abstract: might, however, still affect the transport of charge carriers, thereby limiting the device efficiencies. A very long electron diffusion length, greater than 175 µm, has been reported for a CH 3 NH 3 PbI 3 single crystal (SC); [7] it decreases to ≈100 nm in polycrystalline films, due to these traps. [8] Therefore, higher efficiencies are expected for PeSCs incorporating perovskite SCs. Indeed, SC perovskitebased electronic devices have attracted much attention recently. [7,[9][10][11][12][13][14][15][16][17][18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 27 publications
0
49
0
Order By: Relevance
“…To date, the inverse temperature crystallization method has been widely evidenced as a universal procedure for the fabrication of various bulk halide‐perovskite single crystals as well as single‐crystal MAPbBr 3 thin film, while the applicability of this method towards growing narrow‐bandgap iodine‐based single‐crystal perovskite (such as MAPbI 3 ) thin films is challenging. Yue et al found that the difficulties in single‐crystal MAPbI 3 film preparation originated from a high nucleation‐energy barrier owing to the distinct solubilities of MAI and PbI 2 in GBL. To solve this obstacle, MAPbI 3 seed crystals were introduced into the confined space to bypass the nucleation barrier, and single‐crystal MAPbI 3 thin films with thicknesses of 50 μm and lateral dimensions of up to 2 mm were obtained through the inverse temperature crystallization process …”
Section: Fabrication Methods For Perovskite Single‐crystal Thin Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the inverse temperature crystallization method has been widely evidenced as a universal procedure for the fabrication of various bulk halide‐perovskite single crystals as well as single‐crystal MAPbBr 3 thin film, while the applicability of this method towards growing narrow‐bandgap iodine‐based single‐crystal perovskite (such as MAPbI 3 ) thin films is challenging. Yue et al found that the difficulties in single‐crystal MAPbI 3 film preparation originated from a high nucleation‐energy barrier owing to the distinct solubilities of MAI and PbI 2 in GBL. To solve this obstacle, MAPbI 3 seed crystals were introduced into the confined space to bypass the nucleation barrier, and single‐crystal MAPbI 3 thin films with thicknesses of 50 μm and lateral dimensions of up to 2 mm were obtained through the inverse temperature crystallization process …”
Section: Fabrication Methods For Perovskite Single‐crystal Thin Filmsmentioning
confidence: 99%
“…Yue et al found that the difficulties in single‐crystal MAPbI 3 film preparation originated from a high nucleation‐energy barrier owing to the distinct solubilities of MAI and PbI 2 in GBL. To solve this obstacle, MAPbI 3 seed crystals were introduced into the confined space to bypass the nucleation barrier, and single‐crystal MAPbI 3 thin films with thicknesses of 50 μm and lateral dimensions of up to 2 mm were obtained through the inverse temperature crystallization process …”
Section: Fabrication Methods For Perovskite Single‐crystal Thin Filmsmentioning
confidence: 99%
“…However, a number of key problems, such as the lack of resistance to water, light and heat, and many grain boundaries and defects of polycrystalline and nanocrystalline thin films, have hindered large‐scale industrial production of PSCs. PSCs with single‐crystal thin film as the light absorption layer have mainly been constructed with MAPbI 3 5, 96 and MAPbBr 3 6, 97, 98 . Although the PCE of 3D single‐crystal PSCs has increased rapidly to 21.09% in the past 23 years, it is still far lower than that of polycrystalline silicon cells 99–101 …”
Section: Methods Of 2d Perovskite Crystallizationmentioning
confidence: 99%
“…Polycrystalline semiconductors generally exhibit poorer electronic or optoelectronic properties compared to their single‐crystal counterparts . For example, it is reported that single crystals of hybrid organic–inorganic halide perovskite CH 3 NH 3 PbI 3 , a promising high‐efficient photovoltaic (PV) absorber, are far superior to their polycrystalline thinfilm counterparts in terms of trap‐state density, carrier diffusion length, lifetime, and carrier mobility .…”
Section: Introductionmentioning
confidence: 99%